ANALISIS JENIS DAN MAKNA METAFORA DALAM NOVEL BUYA HAMKA KARYA A. FUADI - Ana Melia; Isnaini Leo Shanty; Suhardi; Abdul Malik; Dody Irawan; Tessa Dwi Leoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of figurative language in literary works plays an important role in conveying messages and enhancing aesthetic value. However, the use and interpretation of metaphors often require deeper understanding so that the author’s intended message can be fully comprehended. This study aims to identify and describe the types and meanings of metaphors found in the novel Buya Hamka by A. Fuadi. This research employed a descriptive qualitative approach. The researcher served as the primary research instrument, supported by a data analysis guideline. The research data consisted of words, phrases, and sentences containing metaphorical expressions. Data were collected through reading, note-taking, and classifying the data into an inventory table, while data validity was ensured through triangulation techniques. The data analysis procedures included data reduction, data display, and conclusion drawing. The findings reveal a variety of metaphorical expressions used throughout the novel. The types of metaphors identified include anthropomorphic metaphors, animal metaphors, concrete-to-abstract metaphors, and synesthetic metaphors. In terms of associative meaning, four categories of metaphorical meaning were identified, namely connotative meaning, stylistic meaning, affective meaning, and reflective meaning. The study concludes that the diversity of metaphor types and meanings in the novel Buya Hamka enriches its aesthetic value while strengthening the expression of emotions and characterization within the narrative